A QoS capable architecture for IEEE 80211 wireless LAN and the prototype implementation on Linux - Liu, Dong (University of Ottawa (Canada), 2008)
The increasing popularity of wireless handheld devices with multimedia functionality and IEEE 802.11 based network connectivity generated the need for Quality of Service (QoS) support of real time applications deployed over the wireless LANs. However, the time varying nature of wireless link and network is a serious challenge when attempting to provide Quality of Service support. This thesis proposes a low cost/complexity QoS capable wireless LAN architecture. We designed a distributed network congestion control scheme based on current commercial available hardware. The proposed technique was implemented on a Linux based testbed. Its performance was assessed through extensive experiments. Our evaluation test work includes two parts. First an IEEE802.11b wireless LAN testbed is established and a thorough network capacity measurement test is performed. The actual performance of real wireless LAN products is evaluated in a typical indoor environment. Furthermore, the impacts of multiple competing stations and nearby radio noise are also evaluated in this testbed. In the second part, the QoS capable wireless architecture prototype is implemented using Linux operating system Redhat 7.3 and Orinoco Golden IEEE802.11b wireless network card. The performance evaluation is conducted using the prototype implemented on the IEEE802.11 b wireless LAN testbed.
Keywords: Engineering, Electronics and Electrical.; Computer Science.